Pengaruh Kebijakan Dividen Terhadap Nilai Perusahaan Dengan Profitabilitas Sebagai Variabel Intervening Pada Perusahaan LQ45 Yang Terdaftar Di Bursa Efek Indonesia Tahun 2019-2021 - Sephia Sephia; Mutmainah Mutmainah; M. Ichsan Diarsyad (Universitas Katolik Widya Karya Malang, 2023)
This study aims to determine the speculative choices made by funders to increase company self-esteem considering the presentation of LQ45 organizations listed on the Indonesia Stock Exchange in 2019-2021 by looking at the impact of financial proportions. When deciding to invest in the capital market, an investor must choose the right company. so investors can choose the company with the help of market ratio analysis. Dividend Policy and Profitability become mediating variables for this ratio. The inspection strategy used in this exploration is quantitative exploration and uses additional information gathering procedures as an annual report. Sampling in this study used a purposive sampling strategy consisting of 20 LQ45 businesses that met the sample criteria. Path analysis and linear regression analysis are the methods used for data analysis. Testing is done either bit or intercession. The consequence of this study reveals that the side effect of this study states that profit and profit strategies affect firm value. Meanwhile, Profit Strategy has a significant effect on Benefit. Mediation The effect of dividend policy on firm value cannot be mediated by profitability..